Design and realization of a high-speed traffic collection and processing scheme for campus networks using FPGA - YAO Renlong; ZHAO Qiong; HE Haitao; WEI Yujun; LI Enlei (Tongxin xuebao)
The study captures the entire traffic data stream of the campus network using the SDN architecture, followed by parsing and processing with FPGA technology to generate application-level log data at different levels. Subsequent analysis and mining with big data techniques provide data support for campus network management and security, revealing potential risks within the network.